Ivacaftor improves rhinologic, psychologic, and sleep‐related quality of life in G551D cystic fibrosis patients. Issue 3 (24th November 2018) - McCormick, Justin; Cho, Do‐Yeon; Lampkin, Brooks; Richman, Joshua; Hathorne, Heather; Rowe, Steven M.; Woodworth, Bradford A.
Abstract : Background: Ivacaftor is a cystic fibrosis transmembrane conductance regulator (CFTR) potentiator that improves pulmonary function in cystic fibrosis (CF) patients with at least 1 copy of the G551D CFTR mutation. The purpose of this study is to evaluate the impact of ivacaftor on chronic rhinosinusitis (CRS) symptoms in this population. Methods: The G551D Observational (GOAL) study was a multicenter prospective cohort study enrolling CF patients ≥6 years with at least 1 G551D mutation. Subjects were provided 20‐item Sino‐Nasal Outcome Test (SNOT‐20) questionnaires prior to ivacaftor therapy and at 1, 3, and 6 months afterward. The impact on rhinologic (R), psychological (P), sleep (S), and ear/facial (E) quality of life (QOL) domains was evaluated separately. Results: Of 153 subjects, 129 (84%) completed all questionnaires. Typical baseline symptom burden was low (75% with scores <1) and degree of improvement (ie, reduced scores) was greater with higher baseline scores. SNOT‐20 decreased, reflecting improvement, at all follow‐up intervals (1 month: [mean change ± standard deviation] –0.25 ± 0.53, p < 0.01; 3 months; –0.29 ± 0.58, p < 0.01; 6 months: –0.21 ± 0.58, p = 0.02), but less than the prespecified minimal clinically important difference (0.8). Significant improvement was observed at 1, 3, and 6 months in the R domain (1 month: –0.24, p < 0.01; 3 months: –0.34, p < 0.01; 6 months: –0.25, p < 0.01) and P domain (1 month: –0.25, p < 0.01; 3 months: –0.32, p < 0.01; 6 months: –0.26, p < 0.01), and 1 and 3 months in the S domain (1 months: –0.35, p < 0.01; 3 months: –0.32, p < 0.01; 6 months: –0.18, p = 0.07). There was no improvement in the E domain at any time point. Conclusion: Ivacaftor improves QOL in the R, P, and S domains in G551D CF patients, although QOL instruments validated for CRS may not translate well to CF CRS patients because symptom burden was surprisingly low.